Boosting hydrogen production in ultrathin birnessite nanosheet arrays-based electrolytic cell by glycerol and urea oxidation reactions. (December 2022) - Ruan, W.; Yuan, C.; Teng, F.; Liao, H.; Ibhadon, A.O.
Abstract: It is still a big challenge to develop an innovative strategy to overcome sluggish oxygen evolution reaction (OER). Herein, ultrathin birnessite@nickel foam nanosheet array (KMO@NF) with oxygen vacancy (VO ) is prepared by an in-situ growth method. KMO@NF shows a high activity for water splitting because VO and Mn 3+ favor the adsorption of OH − and H2 O. Furthermore, glycerol oxidation reaction (GOR) and urea oxidation reaction (UOR) are employed to substitute for OER to improve hydrogen evolution reaction (HER). Compared with OER, the anodic current densities of GOR and UOR have increased by 19.34 and 18.04 times at 1.43 V ( vs . reverse hydrogen electrode (RHE)), respectively. To reach the same current density of 30 mA/cm 2, the required cell voltages for UOR- and GOR-based electrolytic cells have decreased by about 16% than that of water-based electrolytic cell (2.024 V), meaning that to produce the same amount of hydrogen, about 16% of electric energy can be economized. Besides, the Faradaic efficiencies of UOR- and GOR-based electrolytic cells (95% and 97%) are higher than that of water-based electrolytic cell (92%), confirming a higher conversion of energy. The innovative system can not only produce hydrogen efficiently, but also effectively degrade environmental pollutants. Graphical abstract: Hydrogen evolution reaction (HER) efficiency is greatly enhanced by the substitution of glycerol oxidation reaction (GOR) or urea oxidation reaction (UOR) for sluggish oxygen evolution reaction (OER). To produce the same amount of hydrogen, about 16% of electric energy can be saved in the innovative electrolysis cell than conventional water electrolysis cell. Image 1 Highlights: Ultrathin birnessite@nickel foam nanosheet array is obtained by an in - situ growth method. Hydrogen production efficiency is greatly enhanced by adding urea or glycerol in electrolyte. Whole cell voltage has decreased by more than 16% while adding urea or glycerol. To produce the same amount of hydrogen, about 16% of electric energy can be saved for the electrolysis cell. Synergistic hydrogen production and pollutant degradation can be achieved.